Demand feeding device using a video processing system and fish behavior as parameter for a computer program to control feeding time and amount - Mukai, Yukinori; Taha, Zahari; Saad, Shahbudin; Sallehudin, Muhammad Firdaus; Nai, Han Tan; Ismail, Khairul Muttaqin; Mohd Razman, Mohd Azraai; Adnan, Faiez Azizi (2018)
Fish feeding system has three methods; manual, automatic and demand feeding. Demand feeding system serves feeds to fish, when fish switch on feeders. Although demand feeding system has advantages, there are still some problems; e.g. social status in fish. A few fish occupy the actuation of switch of the feeder, so results show the variation in fish growth. Another issue is that the fish learning period of demand feeders becomes long depending on fish species. New type feeding system was developed to overcome these problems related to feeding to fish. The new feeding system uses fish behaviour as sensor to control feeding device. In general when fish are hungry and not hungry, their behaviours are different. In this system, CCD cameras detected fish behaviour and computer program analysed the differences of behaviour, then the programed decided and transmitted the order to feeding device to start feeding or stop feeding. Asian seabass young were used for feeding test of this feeding system. Control experiments were prepared with timer feeder and infrared feeding system. Glass aquaria (45 cm x 45 cm x 90 cm) were prepared with each feeding system and water filtration system. Each system was prepared triplicate aquaria. Feeding experiment results showed no significant difference among each feeding system, however the experiment showed the new feeding system could provide the feed to fish smoothly and it can be used for fish rearing.